SYSTEMATICS OF THE HADITH PERSPECTIVE ON THE PHENOMENON OF ONLINE GAMBLING - Andi Fadhil Andi Aderus; Abdul Rahman Sakka; Siti Aisyah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The term "khitbah" refers to the rituals involved in proposing marriage between a man and a woman, or between a man and a woman. The words "khitbah" (proposing) and "zawaj" (marrying/getting married) are defined differently in all hadith volumes. Similarly, conventions distinguish between males who are engaged and those who are married, and the Shari'ah makes a clear distinction between the two. Just as the Qur'an discusses marriage (including proposals), the Prophet's hadith also describes marriage proposals, which is the first step in continuing the practice to the level of marriage, and the author here presents a thematic interpretation study of the hadith pertaining to sermons.